Influence Of Ph And Different Emulsion Components On Stability And Physicochemical Properties Of Canola Oil-In-Water Emulsion - Rasnani, Negar Mohammadian (2010)

(untitled)
The main objective of the present study was to investigate the effect of pH (5-7), processing conditions (i.e. pressure, cycle and temperature) and main emulsion components (namely, propylene glycol, caseinate sodium, pectin, sodium chloride and canola oil) on the physicochemical properties of sodium caseinate-pectin stabilized emulsions. In this work, the physicochemical emulsion properties assessed by measuring the zeta-potential, average droplet size, apparent viscosity, turbidity, and creaming stability were considered as response variables. The results indicated that the pH and temperature had significant (p < 0.1) effects on all the response variables studied. The highest creaming stability was observed at pH 5, which was attributed to the formation of multilayer in the interfacial area. It was found that the average droplet size increased when pH was increased from 5 to 7. The prepared emulsions showed shear-thinning behaviour at different pH values (5-7). The highest emulsion viscosity was also observed at pH 5; while it decreased when pH was increased from 5.5 to 7. The influence of processing conditions (i.e. pressure, cycle of high pressure homogenizer and temperature of environment to solubilize the pectin) on the physicochemical properties of sodium caseinate-pectin stabilized emulsions were investigated. The results indicated that the independent variables had the most and least significant (p < 0.05) effect on average droplet size and stability, respectively. The effect of cycle of the homogenizer was significant (p < 0.05) in all response variables. The nonlinear regression equations were significantly (p < 0.05) fitted for predicting the changes in all the response variables with relatively high coefficient of determination (R2 > 0.825). It was concluded that desirable physicochemical properties can be achieved when the pressure, cycle, and temperature of the pectin solution were adjusted to 13 MPa, 3, and 80 ° C, respectively. It was observed that the physicochemical properties of emulsions were significantly (p < 0.1) influenced by the concentration of pectin. It could be explained by the fact that the presence of carboxyl groups (–COOH) in the molecular structure of pectin provided the proper surface activity in the interfacial area. The pectin molecules adsorbed to the droplet surfaces and increased the repulsion forces between the emulsion onto droplets, thereby preventing extensive droplet flocculation. The zeta potential remained negative in all emulsion samples, possibly because of negatively charged (-COO-) groups presence in the molecular structure of pectin. The second order regression equations were significantly (p < 0.1) fitted for predicting the changes in all the response variables with relatively high coefficient of determination (R2 > 0.7). The results indicated that the emulsion containing 0.9% (w/w) propylene glycol, 1.0% (w/w) sodium caseinate, 3.0% (w/w) pectin, 0.2% (w/w) sodium chloride and 15.0% (w/w) canola oil provided the optimum emulsion formulation with desirable physicochemical properties. The adequacy of response surface equations was confirmed by indicating no significant (p > 0.1) difference between the experimental and predicted values.